The perfectibility of human nature in eastern and western thought - Coward, Harold G. (SUNY series in religious studies, 2008)
The perfectibility of human nature in western thought -- The perfectibility of human nature in western philosophy and psychology -- The perfectibility of human nature in Judaism -- The perfectibility of human nature in Christianity -- The perfectibility of human nature in Islam -- The perfectibility of human nature in eastern thought (arising in India) -- The perfectibility of human nature in eastern philosophy and yoga psychology -- The perfectibility of human nature in Hinduism -- The perfectibility of human nature in Buddhism